(untitled) (Práxis Educativa, 2025)
This article presents an unpublished interview conducted with Zygmunt Bauman in 2015 at his home in Leeds, United Kingdom. The conversation explores the relationships between culture, education, and the social transformations of liquid modernity, revealing a thinker attentive to the uncertainties of the present yet still confident in humanity’s ability to reinvent itself. Bauman reflects on the dissolution of cultural boundaries, the impact of globalization on identity formation, and the challenges faced by education in the context of contemporary economic and symbolic fluidity. He argues that culture, once conceived as a stable system, has become a flow of global influences, and that education, increasingly subjected to market logic, risks losing its ethical and emancipatory dimensions. The interview also addresses the fragmentation of knowledge and the weakening of the welfare state as symptoms of a society searching for direction. By bringing together theory and lived experience, the text highlights the continuing relevance of Bauman’s thought for understanding today’s educational dilemmas and invites readers to rethink education as a space of resistance and hope amid contemporary liquidity. Keywords: Culture. Education. Liquid modernity. Globalization. Zygmunt Bauman.